Combined Fronto-orbital Contouring and Orthognathic Surgery in Craniometaphyseal Dysplasia - Bruno Nifossi Prado, DDS, MSc; Lucas Cavalieri-Pereira, DDS, PhD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Craniometaphyseal dysplasia is a rare congenital sclerosing skeletal dysplasia that presents with facial dimorphism and is clinically described by prominent supraorbital bridges, severe retrognathia, and respiratory problems. Fronto-orbital cranioplasty is necessary to achieve satisfactory aesthetic outcomes. The supraorbital arches were exposed to the nasal bone through coronal access, with the help of a saw and a wear drill, and osteotomy of the frontal and orbital regions with hyperostosis was performed. Our case report describes a rare and difficult to diagnose case with a few publications of a 24-year-old female patient, who presented with metaphyseal dysplasia associated with mandibular retrognathia. As a treatment, fronto-orbital cranioplasty was performed in association with orthognathic surgery. The resolution of the case resulted in excellent functional and aesthetic results, indicating that frontal cranioplasty associated with orthognathic surgery is a plausible treatment for facial dimorphism through craniometaphyseal dysplasia.